MODELING COMPETENCE AND MODELING METHODS IN ARTISTIC CERAMICS - CARP, MARIANA (Studiul Artelor şi Culturologie: Istorie, Teorie, Practică, 2022)
The whole educational system is gradualy reoriented towards the paradigm oriented towards practical activity, and the desired qualities of the student are represented in the form of competences. In artistic higher education, the main purpose of the subjects within the course Artistic Ceramics is to form the student’s modeling and artistic-technological skills and competences. In the process of artistic creation, for the creation of artistic ceramics, an important objective is being achieved, which provides for the training of students in creative, artistic and pedagogical self-organization of activity based on views regarding the decorative, creative specifics, skills and competences of working with ceramic materials